ANALISIS STRATEGI PENGEMBANGAN OBYEK WISATA AIR TERJUN TUMPANG DUA DI KABUPATEN KOTABARU KALIMANTAN SELATAN - Rika Sylvia (Universitas Muhammadiyah Kalimantan Timur, 2017)
Kotabaru District is one part of South Kalimantan Province, which has an area of 9422.46 km2 (more than ¼ Kalimantan) and consists of one large and 110 small islands and coastal Length 825 Km. Where there are 12 natural attractions that exist in Kotabaru district, one of which is Air Terjun Tumpang Dua are located in the village of Sebelimbingan District of North Sea Island. So that the potential of tourism in this area is very potential to be developed to the fullest, because tourism is part of economic activity. The purpose of this study is to analyze the development of appropriate strategies to be applied in tourism in Air Terjun Tumpang Dua of Kotabaru district, where the sampling is done accidental sampling method. Based on the results of alternative research strategies that will be used is to improve the image of tourism products in order to compete with other attractions, improving the cleanliness and maintenance of facilities that already exist, add the facility/ tourist supporting facilities are still lacking, realize the development of tourism by government, improve the environmental quality of the tourist area, and effective promotional activities.